The Evolution of Cytogenetic Traits in Cuscuta (Convolvulaceae), the Genus With the Most Diverse Chromosomes in Angiosperms - Ibiapino, Amalia; García, Miguel A.; Amorim, Bruno; Baez, Mariana; Costea, Mihai; Stefanović, Saša; Pedrosa-Harand, Andrea (Frontiers in Plant Science, 2022)
Karyotypes are characterized by traits such as chromosome number, which can change through whole-genome duplication and dysploidy. In the parasitic plant genus Cuscuta (Convolvulaceae), chromosome numbers vary more than 18-fold. In addition, species of this group show the highest diversity in terms of genome size among angiosperms, as well as a wide variation in the number and distribution of 5S and 35S ribosomal DNA (rDNA) sites. To understand its karyotypic evolution, ancestral character state reconstructions were performed for chromosome number, genome size, and position of 5S and 35S rDNA sites. Previous cytogenetic data were reviewed and complemented with original chromosome counts, genome size estimates, and rDNA distribution assessed via fluorescence in situ hybridization (FISH), for two, seven, and 10 species, respectively. Starting from an ancestral chromosome number of x = 15, duplications were inferred as the prevalent evolutionary process. However, in holocentric clade (subgenus Cuscuta), dysploidy was identified as the main evolutionary mechanism, typical of holocentric karyotypes. The ancestral genome size of Cuscuta was inferred as approximately 1C = 12 Gbp, with an average genome size of 1C = 2.8 Gbp. This indicates an expansion of the genome size relative to other Convolvulaceae, which may be linked to the parasitic lifestyle of Cuscuta. Finally, the position of rDNA sites varied mostly in species with multiple sites in the same karyotype. This feature may be related to the amplification of rDNA sites in association to other repeats present in the heterochromatin. The data suggest that different mechanisms acted in different subgenera, generating the exceptional diversity of karyotypes in Cuscuta.